Barriers to osteopathic manipulative medicine use: A qualitative study of physician attitudes and experiences - Stephen K. Stacey; Kelsie M. Prins; Sydney A. Anderson; Alessandro Quartiroli (PLoS ONE, 2025)
Purpose Despite growing recognition of osteopathic manipulative medicine (OMM) as an effective treatment for chronic pain, little is known about the real-world barriers clinicians face when attempting to integrate OMM into their clinical practice. Fewer than half of practicing Doctors of Osteopathic Medicine (DOs) incorporate OMM into patient care. Understanding the barriers that hinder OMM use is critical to bridging this gap and expanding access to this evidence-based treatment. Methods A survey was distributed to DOs from Mayo Clinic and Mayo Clinic Health System, inviting volunteers for semi-structured interviews about their attitudes and experiences with OMM. The interviews were audio-recorded, professionally transcribed, and analyzed using inductive reflexive thematic analysis. A thematic map was developed through investigator triangulation to connect key themes and subthemes. Results Among 27 survey respondents who volunteered, 16 completed in-depth interviews, representing diverse clinical roles and experiences. Analysis identified six overarching themes: system, capability, utility, training, attitudes and beliefs, and resources. These themes were supported by direct quotes and linked through subthemes that illustrated nuanced barriers and facilitators influencing OMM integration. Conclusions This study provides important qualitative insights into how DOs perceive the systemic, practical, and perceptual barriers that hinder implementation of OMM into clinical practice. Time constraints, scheduling complexity, and limited patient awareness emerged as significant barriers, compounded by broader systemic issues such as patient panel management and practice autonomy. Addressing these barriers through intentional support from institutional leadership could improve access to this valuable treatment.